Interpretation of non-standard words in poetic discourse: examples of Kazakh poetry - Aigul Bizhkenova, Samal Aubakir,; Kapenova, Zhanarsyn; Beibytnur Zhumabekova, Saltanat Aubakirova, (Opción, 2019)
We present a study that investigates the verbal association of poetry in expert and non-expert readers. The associative Theory of Linguistic Creativity is used as a methodological tool. As a result, the processive creativity of the reader interpreting multi-meaningful poetic utterance is directed by linguistic mechanisms used by the poet for de-canonizing linguistic units‟ form and function and constructive principles of the poet‟s modeling of the verbal associative context. In conclusion, the choice of the „right‟ words always remain for the poet one of the priorities.